1991
DOI: 10.1148/radiology.179.2.2014305
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow: ultrasmall superparamagnetic iron oxide for MR imaging.

Abstract: An ultrasmall superparamagnetic iron oxide (USPIO) preparation was evaluated as a potential intravenous contrast agent for magnetic resonance (MR) imaging of bone marrow. One hour after administration of USPIO (40, 80, and 160 mumols of iron per kilogram body weight) in rats and rabbits, T1 and T2 relaxation times were, respectively, approximately 30%, 50%, and 65% lower than precontrast relaxation times. Maximum decrease in relaxation times of marrow occurred within 1-24 hours after intravenous administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 0 publications
4
56
0
Order By: Relevance
“…Khurana et al as the liver (31,32), the spleen (31), lymph nodes (32,33), and bone marrow (34)(35)(36). The relatively large nanoparticles, which have a size on the order of plasma proteins, initially distribute in the blood pool, where they cause strong T1 and T2 relaxation time enhancement (37).…”
Section: Molecular Imaging: Mr Imaging Monitoring Of Macrophage Migramentioning
confidence: 99%
“…Khurana et al as the liver (31,32), the spleen (31), lymph nodes (32,33), and bone marrow (34)(35)(36). The relatively large nanoparticles, which have a size on the order of plasma proteins, initially distribute in the blood pool, where they cause strong T1 and T2 relaxation time enhancement (37).…”
Section: Molecular Imaging: Mr Imaging Monitoring Of Macrophage Migramentioning
confidence: 99%
“…The immature bone marrow of the New Zealand white rabbit is a model well suited for the current study since hematopoietic marrow is found within the central skeleton and its MR appearance has been well described before. 32,33 In addition, good anatomical resolution can be achieved for rabbits using a clinical MR scanner, which would not have been possible for smaller rodents. Our findings still have to be confirmed in humans.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…It was di‹cult to detect normal hematopoietic cells, including macrophages, in the histologicalˆndings of the rabbit model of bone tumor, whereas pseudoeosinocytes acting as macrophages were seen in in‰ammatory models. 9 Although tumor cells occupied the bone marrow in bone metastasis, and thus, SPIO was not taken up by neoplastic bone marrow in clinical cases, 7,16 in general, macrophages are generated in bone marrow with in‰ammation. 17 As a result, the signal intensity of bone marrow decreased in the osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies using animal models report that SPIO particles were taken up in the bone marrow and signiˆcantly decreased relaxation time of tissue to improve diagnostic ability for focal lesions occurring within 1 to 24 hours or 2 hours. 7,8 We recently reported the potential of SPIO in diŠerentiating between metastasis and osteomyelitis at 24 hours post administration in a rabbit model; we used ferucarbotran, an SPIO particle used clinically as a liver-speciˆc contrast agent. The values show mean±SD (n=5).…”
Section: Introductionmentioning
confidence: 99%